Foot‐and‐Mouth Disease in pigs: current epidemiological situation and control methods - Leon, Emilio Arnaldo (2012)
Foot‐and‐mouth disease (FMD) is the paradigm of a transboundary animal disease. Beyond any doubt, it is the most serious challenge for livestock’s health. Official Veterinary Services from free countries invest considerable amount of money to prevent its introduction, whereas those from endemic countries invest most of their resources in the control of the disease. A very important volume of scientific production is developed every year in different aspects of FMD, and for that reason, the current knowledge makes the diagnosis of the disease easier to a great extent. However, FMD is still endemic in about two‐thirds of the countries, and periodically re‐emergent in several countries. This paper is a review of recent publications, focusing mainly on control measures and current world epidemiological situation, emphasizing primarily pigs.